Pudarnya Batas Kepemilikan Pribadi: Tinjauan Antropologis Terhadap Pengelolaan Kelapa Di Namalomin - Ode Zulkarnain Sahji Tihurua; Muhammad Kashai Ramdhani Pelupessy (IAIN Ambon, 2021)
This study seeks to understand and explain, why is the understanding and practice of the Namalomin community on the island of Seram Laut towards the limits of private ownership-on coconut management so faded? and why is ownership of the tree so strict while the fruit is so loose? The research method that the author uses is the ethnographic method. To explain the loose form of private ownership, the author uses David Graeber's argument about the principle of care and sharing of private property. Meanwhile, to explain why private ownership of the tree is strict, while the fruit from the tree is loose, the author uses the concept of an arboreal-based subsistence economy, while for the fruit from the tree it is loose, the author uses the concept of arboreal-based subsistence economy from David Kyle Latinis. The findings and analysis of this research show that the faded understanding and practice of private ownership is an attempt by coconut tree owners to distribute their ownership to other people – which in the context of the Namalomin community is intended primarily for women. Meanwhile, loose ownership of coconuts is an implication of using the arboreal-based subsistence economy model. Keywords: coconut management; private ownership; the principle of sharing ownership; arboreal-based subsistence economy.